Retrospective observational study of the association between changes in physical activity and frailty in middle-aged and older adults: evidence from the Korean Longitudinal Study of Aging (2006–2022) - Eun-Cheol Park; Ye Jun Jung; Junhyuk Kim; Yun Seo Jang (BMJ Open)
Objectives This study aimed to investigate the relationship between changes in physical activity and frailty among middle-aged and older adults in Korea, using panel data from the 2006–2022 Korean Longitudinal Study of Aging (KLoSA).Design Retrospective observational study.Setting For this longitudinal panel study, data were sourced from the KLoSA dataset.Participants We analysed data from 5594 participants (2855 males and 2739 females) extracted from KLoSA data collected between 2006 and 2022.Primary and secondary outcome measures The frailty index was calculated based on 6 clinical domains comprising 34 age-related health deficits. Changes in physical activity were categorised as persistently inactive, decreased, increased or persistently active. Logistic regression analysis using generalised estimating equations was conducted to assess the association between changes in physical activity and frailty.Results The persistently active group (OR=0.45, 95% CI: 0.40 to 0.50) showed a lower likelihood of frailty than did the persistently inactive group. In the group that increased their physical activity, the OR was 0.57 (95% CI: 0.52 to 0.63), and higher ORs were observed for current smokers and those residing in rural areas.Conclusions This study demonstrated that persistent and increased physical activity is associated with lower frailty in middle-aged and older adults in Korea. Therefore, participation in physical activity in the older adults is one of the important ways to prevent frailty.